The Implementation of Presidential Decree on Gender Mainstreaming: Insight from IAIN Ponorogo - Rohmah Maulidia (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
This paper examines universities' role in achieving Sustainable Development Goals (SDGs) targets by conducting field research and using a policy theory approach. Theoretically, the successful policy implementation depends on several aspects such as communication, the availability of resources, the disposition, and the character of the bureaucracy. This study found that the State Institute for Islamic Studies (IAIN) Ponorogo contributed to implementing SDGs, especially in quality education and strengthening gender equality. However, the institution did not explicitly formulate other SDGs goals. Communication between the Institute for Research and Community Service (LPPM) as the leading sector for gender mainstreaming and leadership is manifested in the strategic plan and formal and informal meetings. Resources owned by IAIN Ponorogo in human resources and social capital are sufficient, which can be found from the active involvement of mass organizations of Fatayat, Muslimat, and Aisiyah in gender strengthening activities. The rector of IAIN Ponorogo is collaborating with the Ministry of Women and Child Protection (KemenPPPA) in realizing gender equality implementation agendas. Meanwhile, the bureaucratic structure that has been developed so far tends to be egalitarian and democratic. In preparing the Strategic Plan and the Master Plan (RIP), IAIN held a hearing with IAIN Ponorogo stakeholders, including the Academic Senate, which provides considerations for higher education policies. The problem is that the IAIN Ponorogo leader has not intensively monitored the targets for achieving gender equality, especially the other targets for achieving the SDGs. Tulisan ini mengkaji lebih dalam bagaimana peran perguruan tinggi dalam pencapaian target SDGs, dengan cara melakukan field research dan menggunakan pendekatan teori kebijakan. Secara teoritik kesuksesan kebijakan sangat tergantung pada beberapa aspek seperti komunikasi, adanya sumber daya, disposisi dan watak birokrasi. Kajian ini menemukan bahwa IAIN Ponorogo turut berkontribusi melaksanakan pembangunan berkelanjutan, khususnya pada pendidikan berkualitas dan penguatan kesetaraan gender, tetapi belum secara eksplisit merumuskan tujuan SDGs yang lain. Komunikasi antara Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) sebagai leading sector pengarusutamaan gender dengan pimpinan diwujudkan dalam renstra, juga dalam rapat formal maupun informal. Sumber daya yang dimiliki IAIN berupa sumber daya manusia maupun sumber daya sosial (social capital) sangat cukup. Terlihat dari keterlibatan aktif ormas Fatayat, Muslimat, Aisiyah dalam kegiatan gender di kampus. Adapun disposisi dalam arti komitmen dapat dilihat dari LPPM dan pimpinan IAIN menggandeng Kementerian Perlindungan Perempuan dan Anak (KemenPPPA) dalam mewujudkan agenda-agenda implementasi kesetaraan gender. Sedangkan struktur birokrasi yang dikembangkan selama ini cenderung egaliter dan demokratis. Dalam penyusunan renstra dan Rencana Induk Pengembangan (RIP), IAIN melakukan rapat dengar pendapat dengan stakeholder IAIN, termasuk dengan Senat Akademik sebagai lembaga pemberi pertimbangan kebijakan perguruan tinggi. Persoalannya adalah pimpinan lembaga IAIN belum secara intensif melakukan monitoring terhadap target pencapaian kesetaraan gender, terlebih target pencapaian SDGs yang lain. Kajian ini berkontribusi pada gagasan PTKI untuk lebih responsif terhadap SDGs